2022
DOI: 10.18203/2394-6040.ijcmph20220671
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of E. coli as a causative agent of urinary tract infections and its drug susceptibility patterns among pregnant mothers seeking medicare at Kisii teaching and referral hospital, Kenya

Abstract: Background: E-coli, a gram-negative entero-bacteria has been associated with urinary tract infections (UTIs) and antimicrobial resistances in human and animals. This study aimed at establishing the prevalence of E. coli among other bacteria causing UTIs in pregnant women seeking Medicare at Kisii teaching and referral hospital (KTRH), Kenya and to establish the drug susceptibility patterns of the isolated E. coli. Setting-The project was done at Kisii teaching and referral hospital, Kenya.Methods: This hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Multi-drug resistance limits the therapeutic options leading to increased morbidity health care costs [23]. A similar study by [24] in Kisii, Kenya revealed E. coli as the most common organism causing UTI in pregnancy and the isolates demonstrated high resistance to sulfamethoxazole (100%), augumentin (85.8%) and ceftriaxone (71.4%). Our study disagrees with [7] in Burkina Faso where among E. coli isolates resistance rates to ampicillin and cotrimoxazole were (65.8%) and (64.4%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-drug resistance limits the therapeutic options leading to increased morbidity health care costs [23]. A similar study by [24] in Kisii, Kenya revealed E. coli as the most common organism causing UTI in pregnancy and the isolates demonstrated high resistance to sulfamethoxazole (100%), augumentin (85.8%) and ceftriaxone (71.4%). Our study disagrees with [7] in Burkina Faso where among E. coli isolates resistance rates to ampicillin and cotrimoxazole were (65.8%) and (64.4%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli (E. coli) are Gram negative rod-shape facultative anaerobic bacteria belonging to the family Enterobacteriaceae. This organism is widely known as the most common etiological agent of Urinary tract infections (UTIs) causing about 75-80% of the UTIs in both hospital and community setting [1,2,3] .The treatment and control of UTIs are accomplished through therapy with different classes of antibiotics namely; β-lactam, fluoroquinolones, aminoglycosides and sulfamethoxazole/trimethoprim [4] and among the antibiotics mentioned, fluoroquinolones is widely used as empirical treatment of complicated and non-complicated UTIs [5,6] . Fluoroquinolones are synthetic, targeting enzymes involved in bacterial DNA replication [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…pregnant women were positive for Escherichia coli. A higher prevalence was reported in Kenya at 23.5%(21), southeast Ethiopia at 27.3% (22), and south-western Uganda at 28.78%(23). The variation may result from local social norms, environmental factors, personal hygiene expectations, and healthcare utilization patterns.…”
mentioning
confidence: 95%